Systellaspis pellucida - Komai, Tomoyuki; Ohtsuka, Susumu; Yamaguchi, Shuhei; Nakaguchi, Kazumitsu (Zenodo, 2018)
Systellaspis pellucida (Filhol, 1884) [New Japanese name: Sukashi-toge-hiodoshi-ebi] Figs. 4, 5 Restricted synonymy: Acanthephyra pellucida Filhol, 1884: 144, 162 [type locality: North-East Atlantic, 26°20’N, 14°53’W, 782 m; lectotype designated by Crosnier & Forest (1973)]. Acanthephyra affinis Faxon, 1896: 162, pl. 2, figs. 1–3 [type locality: off Granada, 286 m]. Systellaspis lanceocaudata .— Balss 1925: 243, figs. 12, 13. Not Systellaspis lanceocaudata Spence Bate, 1888. Systellaspis affinis .— Calman 1939: 190.— Dennel 1940: 345, figs. 19–28, pl. 25, figs. 4, 5, pl. 26, figs. 1–6; Chace 1947: 39, fig. 3. Syetellaspis pellucida .— Crosnier & Forest 1973: 92, figs. 26c, 27c.— Chace 1986: 67, figs. 34m –o, 35g, h.— Chan & Yu 1986:— Crosnier 1987: 720, figs. 12, 13, 14a, b, 15.— Hanamura 1987: 25, fig. 9c–e; Hanamura & Evans 1994: 52.— Cardoso & Young 2005: 70, figs. 54–58.— Pequegnat & Wicksten 2006: 102.— Hayashi 2007: 77.— Poupin & Corbari 2016: 17, fig. 4g. Material examined . T/ RV “ Toyoshio-maru ”, 2005-04 cruise, stn 5, W of Yoron Island, bottom depth 1005–1014 m, 23 May 2005, ORI net oblique tow, 1 ovigerous female (cl 13.5 mm), CBM-ZC 11281. Colouration in fresh condition (Fig. 4) . Body generally semitransparent with scattered red chromatophores, cephalothorax inside reddish; carapace with purple streaks becoming longer posteriorly (= photophores) aligned adjacent to ventrolateral margin; each pleomere with narrow red line posteriorly. Cornea gray-brown. Antennular and antennal peduncles and flagella semitransparent. Maxilliped 3 generally transparent, distal part of ultimate article reddish, grooming setae on inner surface of distal 2 articles yellow-brown. Pereopods 1 and 2 generally semitransparent, fingers reddish. Pereopods 3 and 4 also generally semitransparent, but proximal parts of carpi dark red. Pereopod 5 propodus and carpus generally dark red except for white distal part of propodus; merus purplish. Pleopods 1–5 generally semitransparent, each with small black ...